Trichoderma and its secondary metabolites improve yield and quality of grapes. (February 2017) - Pascale, A.; Vinale, F.; Manganiello, G.; Nigro, M.; Lanzuise, S.; Ruocco, M.; Marra, R.; Lombardi, N.; Woo, S.L.; Lorito, M.
Abstract: Trichoderma is one of the most studied and applied fungal biocontrol agents. The benefits of these microorganisms to the plant include: suppression of pathogens, growth promotion, enhanced nutrient availability and induction of resistance. The biological activity is related to the variety of metabolites that they produce. These metabolites have been found to directly inhibit the pathogens, increase disease resistance and enhance plant growth. In this study, we have examined the effect of two Trichoderma strains and their secondary metabolites on Vitis vinifera in terms of induction of disease resistance, plant growth promotion and increase of polyphenols or antioxidant activity in the grapes. Applications of T. harzianum M10 or T. atroviride P1, as well as their respective major secondary metabolites, harzianic acid (HA) and 6-pentyl-α-pyrone (6PP), have been conducted in greenhouse by foliar spray or drenching. The treatments suppressed the development of powdery mildew caused by Uncinula necator . In a field experiment, a spore suspension of T. harzianum strain T22 or a 6PP solution was applied until fruit harvest. The results indicated that both T. harzianum T22 and 6PP are able to improve crop yield and increase the total amount of polyphenols and antioxidant activity in the grapes. The effects of the isolated natural compounds were comparable with those obtained by using the living fungus. Graphical abstract: Highlights: Trichoderma strains M10, P1 suppressed powdery mildew development on grape leaves. Trichoderma metabolites HA and 6PP also controlled powdery mildew development. T22 and 6PP promoted plant growth in terms of crop yield. T22 and 6PP increased antioxidant activity and polyphenols content in grape fruits.